Salary Structures in Health Informatics Academia: A Preliminary Survey Analysis - Feldman, Sue S.; Martin, Ben; Jones, Josette; Unertl, Kim M.; Fritts, Madison; Nagy, Paul; Gochnauer, RaeLynn (Applied Clinical Informatics, 2025)
Health informatics continues to be a continuously evolving discipline. As a result, faculty in health informatics training programs cover a broad range of topics and work in highly diverse academic contexts. This is a strength of the field, and also introduces challenges in understanding faculty salary ranges and assessing potential salary disparities across contexts. Although limited studies have been done on salary ranges in specific academic contexts, prior to this, no comprehensive salary survey had been performed on faculty in health informatics.The goal of this study was to obtain a preliminary understanding of the salary ranges for academic health informatics faculty and contextual factors that affect salary ranges in this field.A team of researchers affiliated with the American Medical Informatics Association (AMIA) Academic Forum collaboratively developed a survey focused on salary and factors that affect salary for health informatics faculty. The survey was distributed through official AMIA communication channels, including communications at the 2023 AMIA Symposium. Descriptive statistics were calculated, and an ordinal regression analysis was performed.Of 314 responses, 153 individuals employed by academic organizations reported their base salary information. A majority (61%) of these respondents reported working in a school of medicine, with PhD (59%) and MD (37%) degrees reported as the highest educational level for the majority of the sample. When adjusted for cost of living, there were statistically significant associations between salary and type of school/department, position/title, and highest degree. We also found that while salaries at the assistant professor level were between $120,000 and 159,999, those of associate and full professors were at or above $200,000.The survey provided preliminary baseline data on salary ranges in academic health informatics programs and factors leading to salary differences. More data are needed on focused topics to extend the impact of this type of survey.
Keywords: informatics; salary trends; academic salaries; faculty compensation